Cycloferon Efficacy of Therapy of Chronic Hepatitis B (Results of Randomized Multicentre Study) - T. V. Sologub; A. A. Shuldyakov; L. G. Goryacheva; I. P. Baranova; YU. N. Linkova; A. L. Kovalenko; M. G. Romantsov (Антибиотики и Химиотерапия)
The best therapeutic effect in the treatment of patients with chronic hepatitis B was observed with the use of cycloferon in the scheme of the antiviral therapy. The combination of cycloferon with lamivudine provided complete stable remission in 54.1% of the patients, whereas the use of а-interferon in combination with cycloferon provided remission in 44.1% of the lamivudine-resistant patients. The use of cycloferon in the therapy of chronic hepatitis B made it possible to lower the frequency and manifestation level of the side effects and prevented the lamivudine resistance development and generation of the virus mutants.